2017
DOI: 10.1212/wnl.0000000000003663
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic biomarkers as strong correlates of Parkinson disease progression

Abstract: Metabolomic profiling of plasma yielded strong prediction of PD progression and offered biomarkers that may provide new insights into PD pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
91
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 122 publications
(96 citation statements)
references
References 35 publications
(46 reference statements)
3
91
1
1
Order By: Relevance
“…Among our studies, the CSF compounds corresponding to the diagnosis of PD were not the same biochemicals that were found to correlate with the progression of PD . The latter set of compounds also differed from the metabolomic profile in postmortem CSF specimens discovered to distinguish PD from controls …”
contrasting
confidence: 51%
See 2 more Smart Citations
“…Among our studies, the CSF compounds corresponding to the diagnosis of PD were not the same biochemicals that were found to correlate with the progression of PD . The latter set of compounds also differed from the metabolomic profile in postmortem CSF specimens discovered to distinguish PD from controls …”
contrasting
confidence: 51%
“…Trezzi and colleagues linked their biochemical findings to a plausible explanation for PD pathogenesis implicating oxidative stress. Whereas the search for biomarkers may be rewarded with insights into the disease process (such as involvement of the kynurenine pathway), it also might be a scientific conceit that the altered concentrations of compounds should necessarily point to the mechanisms of neurodegeneration. It seems possible that even the most robust biomarkers chosen by metabolomics might actually be no more than epiphenomena of the disease process.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we and other groups revealed that serum and/or plasma metabolomics are useful for identifying alterations in metabolic pathways associated with the pathological condition of iPD . In iPD, pathological alterations in the peripheral nervous system, such as peripheral vagus nerve degeneration with α‐synuclein deposition, are observed from an early stage.…”
Section: Introductionmentioning
confidence: 99%
“…From this study, Burte et al identified 20 metabolites that were statistically-significant for prediction of PD progression and mild cognitive impairment. In another study, Lewitt and colleagues employed dual UPLC/MS/MS and GC-MS analysis of biofluids from PD patients to identify small-molecule biomarkers [7]. From the nontargeted metabolomics analysis, the authors identified 575 and 383 distinct biomarkers from plasma and CSF samples, respectively.…”
Section: Introductionmentioning
confidence: 99%